APOA II genotypes frequency and their interaction with saturated fatty acids consumption on lipid profile of patients with type 2 diabetes. Issue 4 (August 2016) - Noorshahi, Neda; Sotoudeh, Gity; Djalali, Mahmoud; Eshraghian, Mohamad Reza; Keramatipour, Mohammad; Basiri, Marjan Ghane; Doostan, Farideh; Koohdani, Fariba
Summary: Background & aim: Several studies have suggested that APOA II-265T/C polymorphism affect lipid profile. The aim of this study was to investigate the effect of −265T/C APOA II polymorphism and saturated fatty acids (SFA) intake interaction on lipid profile in diabetic population who are at risk for lipid disorders. Methods: In this cross sectional study, 697 type 2 diabetic patients participated. Food consumption data were collected using validated semi-quantitative FFQ during the last year. Realtime-PCR was used to determine APOA II−265T/C genotypes. The interaction between the genotypes and SFA intake with lipid profile was tested using analysis of covariance (ANCOVA). Results: According to APOA II−265T/C (rs5082) genotype distribution results, CC genotype with a frequency of 12.9% and TC with that of 47.7% showed the lowest and highest frequency in our population, respectively. CC genotype subjects had significantly lower total cholesterol, triglyceride, Cholesterol/HDL-c ratio and non-HDL cholesterol than T allele carriers (p = 0.009, p = 0.02, p = 0.02 and p = 0.002, respectively). The interaction between genotype and SFA intake contributed to significant higher levels of LDL-c and LDL/HDL in CCs (p = 0.05 and p = 0.01), suggesting vulnerability of these individuals to high intake of SFA in the diet. Conclusion: APOA II polymorphism may influence the saturated fatty acid intake required to prevent dyslipidemia in the type 2 diabetic population.